A 2000-yr reconstruction of air temperature in the Great Basin of the United States with specific reference to the Medieval Climatic Anomaly. Issue 2 (September 2014) - Reinemann, Scott A.; Porinchu, David F.; MacDonald, Glen M.; Mark, Bryan G.; DeGrand, James Q.
Abstract: A sediment core representing the past two millennia was recovered from Stella Lake in the Snake Range of the central Great Basin in Nevada. The core was analyzed for sub-fossil chironomids and sediment organic content. A quantitative reconstruction of mean July air temperature (MJAT) was developed using a regional training set and a chironomid-based WA-PLS inference model (r 2 jack = 0.55, RMSEP = 0.9°C). The chironomid-based MJAT reconstruction suggests that the interval between AD 900 and AD 1300, corresponding to the Medieval Climate Anomaly (MCA), was characterized by MJAT elevated 1.0°C above the subsequent Little Ice Age (LIA), but likely not as warm as recent conditions. Comparison of the Stella Lake temperature reconstruction to previously published paleoclimate records from this region indicates that the temperature fluctuations inferred to have occurred at Stella Lake between AD 900 and AD 1300 correspond to regional records documenting hydroclimate variability during the MCA interval. The Stella Lake record provides evidence that elevated summer temperature contributed to the increased aridity that characterized the western United States during the MCA.